Labour Mobility and Regional Disparities: The Role of Female Labour Participation - S. Ederveen; Richard Nahuis; A. Parikh (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2005)
Unemployment rates as well as income per capita differ vastly across the regions of Europe. Labour mobility can play a role in resolving regional disparities. This paper focuses on the questions why labour mobility is low in the EU and how it is possible that it remains low. We explore whether changes in male and female labour participation act as an important alternative adjustment mechanism. We answer this question in the affirmative. We argue that female labour participation is very important in adjusting to regional disparities.
Keywords: 330; Labour Mobility; Labour Participation; European Union; Scientific